Extending the biocatalytic scope of regiocomplementary flavin-dependent halogenase enzymes. Issue 6 (23rd April 2015) - Shepherd, Sarah A.; Karthikeyan, Chinnan; Latham, Jonathan; Struck, Anna-Winona; Thompson, Mark L.; Menon, Binuraj R. K.; Styles, Matthew Q.; Levy, Colin; Leys, David; Micklefield, Jason
Abstract : Targeted mutagenesis increases the activity and alters the regioselectivity of flavin-dependent halogenases. Abstract : Flavin-dependent halogenases are potentially valuable biocatalysts for the regioselective halogenation of aromatic compounds. These enzymes, utilising benign inorganic halides, offer potential advantages over traditional non-enzymatic halogenation chemistry that often lacks regiocontrol and requires deleterious reagents. Here we extend the biocatalytic repertoire of the tryptophan halogenases, demonstrating how these enzymes can halogenate a range of alternative aryl substrates. Using structure guided mutagenesis we also show that it is possible to alter the regioselectivity as well as increase the activity of the halogenases with non-native substrates including anthranilic acid; an important intermediate in the synthesis and biosynthesis of pharmaceuticals and other valuable products.